2015
DOI: 10.1371/journal.pone.0122307
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Genetics of Schistocephalus solidus Parasites in Threespine Stickleback (Gasterosteus aculeatus) from Alaska

Abstract: The nature of gene flow in parasites with complex life cycles is poorly understood, particularly when intermediate and definitive hosts have contrasting movement potential. We examined whether the fine-scale population genetic structure of the diphyllobothriidean cestode Schistocephalus solidus reflects the habits of intermediate threespine stickleback hosts or those of its definitive hosts, semi-aquatic piscivorous birds, to better understand complex host-parasite interactions. Seventeen lakes in the Cook Inl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 65 publications
(81 reference statements)
4
62
0
Order By: Relevance
“…Individual parasites were genotyped by Sprehn et al . (). Fish containing one or more parasites that were successfully genotyped were sequenced and genotyped for the current study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual parasites were genotyped by Sprehn et al . (). Fish containing one or more parasites that were successfully genotyped were sequenced and genotyped for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, comparisons of S. solidus collected from hosts in Oregon and Alaska recovered signatures of divergence (i.e., 1% sequence divergence; Nishimura et al ., ). Several genotypic clusters and significant genetic structure also have been found across south‐central Alaska, possibly due to specificity to the intermediate host or factors limiting definitive host dispersal (Sprehn et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…While the effects of the landscape on gene flow and genetic structure of many animal species have been described (Manel & Holderegger, ; Storfer et al., ), not much is known about how species that are dependent on the movements of other species, as is the case with many parasites, interact with the landscape (Sprehn, Blum, Quinn, & Heins, ). Our study has revealed a difference in the types of land cover that correlate with genetic differentiation of a generalist ectoparasite versus one of its potential bat host species.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneered by work on rabies [11] and chronic wasting disease [12], research has targeted a handful of viruses (reviewed in [13]; see also [14]) and microbes (notably Batrachochytrium dendrobatidis [15]), helminths with direct life cycles [16,17] and their hosts. Systems involving vector-borne pathogens [1821] or several intermediate hosts [22] have been mostly spared from investigation. We believe the application of landscape genetics to vector-borne disease agents, especially including landscape genetic simulation modelling [23] (see Glossary), has significant, underappreciated potential to inform targeted disease control strategies.…”
Section: Parasites Genes and Landscapesmentioning
confidence: 99%